2018
DOI: 10.1016/j.expthermflusci.2017.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Confined and unconfined nucleate boiling of HFE7100 in the presence of nanostructured surfaces

Abstract: A B S T R A C TThis article presents experimental results for the confined and unconfined nucleate boiling of saturated HFE7100 (C 4 F 9 OCH 3 ) at atmospheric pressure and using nanostructured copper discs as heating surfaces. The nanostructures studied consisted of nanoparticles of maghemite (Fe 2 O 3 ) on the heating surface, comprised of a copper disc. Different values for the diameter (10 and 80 nm) and roughness (R a = 0.02 µm and 0.16 µm) were studied. The nanoparticle adhesion on the heating surface pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…In summary, both studies performed by Souza et al [12,13] showed that HTC degradation for coated surfaces depends on the original surface roughness and the nanoparticle diameter ratio. The authors showed that surfaces with high roughness (R a = 0.160 µm) coated with larger nanoparticles diameters (80 nm) have a decrease in the thermal performance in the same way as those surfaces with low roughness (R a = 0.020 µm) coated with smaller nanoparticles diameters (10 nm).…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…In summary, both studies performed by Souza et al [12,13] showed that HTC degradation for coated surfaces depends on the original surface roughness and the nanoparticle diameter ratio. The authors showed that surfaces with high roughness (R a = 0.160 µm) coated with larger nanoparticles diameters (80 nm) have a decrease in the thermal performance in the same way as those surfaces with low roughness (R a = 0.020 µm) coated with smaller nanoparticles diameters (10 nm).…”
Section: Introductionmentioning
confidence: 87%
“…The nucleate boiling regime is one of the most important heat transfer mechanisms even before the pioneering research of Ishibashi and Nishikawa [10] about confined nucleate boiling up to recent studies related to confined boiling and modified surfaces [11][12][13]. The gap size effect can be characterized by a dimensionless number known as the Bond number, Bo, defined as the ratio of the characteristic length to the confined space, s, and the capillary length, L b , proportional to the detachment diameter of the vapor bubble [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several pool-boiling experimental studies [21] (most commonly performed on functionalized copper surfaces and with FC-72 as the working fluid) showed an enhancement of CHF up to 60 % on micro-/ nanostructured surfaces in comparison with bare samples, while extended (finned) surfaces [30] with or without additional micro-/ nanostructures were able to increase the CHF even above 1000 kW/m 2 . In terms HTC values on copper, silicon, stainless steel and aluminum, different experiments on surfaces with significantly increased micro-/ nanoscale roughness demonstrated enhancements of 50-250 % [31][32][33][34][35], highly porous surfaces demonstrated enhancements of 400-500 % [36,37], while up to 8-fold improvements were observed on finned surfaces [38]. It can be summarized that increased surface roughness with appropriate micro-/nanofeatures (including porosity) increases active nucleation site density, bubble frequency and capillary effects (delaying the surface dryout).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, nucleate boiling with pure components and mixtures has been widely investigated and discussed in the literature, both in textbooks [13,15] and scientific papers. There are many works that discuss the mechanisms and characteristics of nucleate boiling [20,29,39,42,45,46] and correlations for predicting the heat transfer coefficient (HTC), either for pure components [14,21,33,34,40] or mixtures [18,41,48,49]. This substantial research effort is justified by the many applications where nucleate boiling is found, such as refrigeration, nuclear energy and space engineering.…”
Section: Introductionmentioning
confidence: 99%